Diffusing the Vir/us: Derek Jarman’s Transmedial Eco-logy as Pharmacopoeia - Andrea Raso (Lea)
Decades after the outbreak of aids, the disease is still a crucial topic in identity politics, as the queer community strives for worldwide recognition. Past guilt-ridden representations of the aids epidemic, much has been done towards a less dehumanizing re-evaluation of those deemed responsible for the spread of the virus, following the footsteps of spokespersons like filmmaker Derek Jarman. With him, medicine and environmental concerns merge as his body and his unenclosed garden become a somato-political manifesto against epistemic violence. This article contends that Jarman’s multimodal art is ecological and historically conscious in representing homosexuality in its collision with medicine and the law. Focussing on the journal Modern Nature, the film The Garden and Jarman’s gardening work, a form of pharmacopoeia surfaces as a material-semiotic resignification of illness in the face of a new subject-object relationship.